Effects of crude oil and gas condensate spill on coastal benthic microbial populations - Kababu, E.; Angel, D. L.; Sisma-Ventura, G.; Belkin, N.; Rubin-Blum, M.; Rahav, E. (Frontiers in Environmental Science, 2022)
Marine sediments are ecologically-important environments that act as a long-term depository for different contaminants from natural and anthropogenic sources. We investigated the response of crude-oil and gas-condensate spills on benthic microbial populations in the oligotrophic southeastern Mediterranean Sea using costume-design benthocosms. Additions of crude oil and gas condensate significantly changed the sediment’s chemical properties, with 2-fold elevated levels of total organic carbon (TOC) and up to ~ 6-fold higher concentration of total polycyclic aromatic hydrocarbons (∑PAHs) relative to unamended sediments. Naphthalene and benzo(a)pyrene were the dominant species comprising the PAHs in both the crude-oil and gas-condensate treatments (29-43% and 26-35%, respectively). Porewater PO43+ drastically declined throughout the experiment, whereas NO2-+NO3- decreased ~100 days post hydrocarbons addition and then increased in the remaining ~100 days till the conclusion of the experiment. This temporal variability in NO2-+NO3- hints that hydrocarbon pollution may affect the interplay between benthic denitrification and N2 fixation, thus affecting nutrient limitation for benthic heterotrophic bacteria and phytoplankton. Moreover, our results show that crude oil and gas-condensate usually lead to a decline in benthic autotrophic microbial biomass (50-80%), while heterotrophic bacterial abundances remained unchanged, and bacterial production rapidly increased (maximal 1600%, crude-oil>gas-cindensate). These effects were prolonged and lasted several months post hydrocarbons addition, highlighting the sediments as a repository for oil contaminants. Amplicon sequencing of the 16S rRNA gene revealed hydrocarbonoclastic bacteria including Methylophaga, Ponticaulis and Alcanivorax genera post crude-oil addition and Actinobacterota 67-14 lineage following gas-condensate amendments. Our results may enable applying a better science-based environmental policy for the benthic marine environment.